Fabrication of dye Rhoeospathacea with concentration variation in dye-sensitized solar cells (DSSC) - Sri Sumardiasih; Agus Supriyanto; C Cari (Universitas Sebelas Maret, 2017)
Dye-sensitized solar cell (DSSC) is a device that directly converts visible light into electrical energy. In this work we used dye was extracted from Rhoeo spathacea. A natural dye was directly mixed with TiO2 anatase to obtain dyed titanium dioxide which can be used as photoanode for DSSC by varying the volume of dye. The first variation is 2 ml dye mixed with 1 ml of TiO2, and the second variation is 3 ml dye mixed with 1 ml of TiO2. The absorbance spectra of the dye and dye titanium dioxide have been investigated by spectroscopy UV-Visible Lambda 25 and the conversion efficiency of dye titanium dioxide used Keithley 2602A meter. The DSSC based on dye titanium dioxide with varying volume of dye showed that the efficiency of the the second variation is 0,033% which is higher than the first variation (0,023%) as obtained from I-V characterization.